KNOWLEDGE, ATTITUDES AND BEHAVIOURS OF TOP JUNIOR RUGBY UNION COACHES TOWARDS TRAINING THE TACKLE. Issue 7 (11th March 2014) - Hendricks, S; Martin, S; Micheal, L
Abstract : Background: Coaching strategies for effective technique and injury prevention have been proposed for the tackle. Despite this, little is known about current knowledge, attitudes and behaviours of coaches towards proper contact technique when training the tackle. Objective: Report on coaches' knowledge, attitudes and behaviours towards coaching the tackle. Design: Questionnaire using a 5-point Likert scale for importance (attitude), quantity (behaviour) and injury risk (knowledge). Field-training sessions were observed during the first 4 weeks of the season. Setting: High school rugby coaches and their respective training sessions. Participants: Top 8 junior rugby coaches in the Western Cape, South Africa. Risk factor assessment: Two sources: (i) from the questionnaire; importance of safety and performance, methods used to train the tackle, resources used to develop coaching knowledge and factors influencing their coaching, (ii) from observing training; number of tackle training sessions, time spent training the tackle, design of tackle training drill, equipment used, instruction and emphasis communicated to players. Main outcome measurements: Knowledge, attitudes, reported behaviours when training proper contact techniques, and observed behaviours for tackle training. Results: Coaches noted the tackle event as a high-risk phase of play (mean risk rating for tackling=3.8, 95% CI 3.3–4.4; ball into contact=3.6, 95% CI 2.6–4.6). Proper contact technique was rated as important and very important for both safety and performance. Of the 96 training sessions observed, 16% (n=15) included tackle training. Conclusions: The coaches in this study were aware that the tackle is a high-risk phase of play, and that coaching proper technique is important for tackling and taking the ball into contact. A positive attitude was shown towards the importance of proper technique in reducing the risk of injury and improving performance. Details on actual tackle training behaviours were revealed, however, it is difficult at this stage to establish whether this is sufficient for match preparation.